Impact of Joint Modeling Approach on Performance Estimates of Older-Type RC Buildings - Bayhan, Beyhan; Ozdemir, Gokhan; Gulkan, Polat (Earthquake Engineering Research Inst, 2017)
The behavior of beam-column connections has usually been ignored in the modeling process due to its complexity and relatively recent awareness of its possible impact on response. This study presents the features of modeling unrein-forced beam-column joints in estimating seismic demands. A representative RC frame is subjected to strong ground motions. Through nonlinear dynamic analyses, base shear, roof displacement, inter-story drift and joint rotation are noted. The dynamic analyses are performed comparatively through two analytical models with rigid and flexible joint assumptions. In the flexible joint model, shear deformation at the beam-column joint and bond-slip deformation at the beam-column interface are simulated through a previously verified analytical representation. Results indicate that introducing unreinforced beam-column joint behavior to the model may lead to almost two times larger seismic demands compared to those obtained from rigid connection assumption. Thus, the performance assessment of such buildings may conclude erroneously with underestimated seismic demands and damage levels when inelastic actions in the joints are ignored. However, in some cases, lower seismic demands can also be obtained for the flexible joint model.
Keywords: [No Keywords]